Tidig hållfasthet för sprutbetong och cementingjuten bergbult - Swedberg, Erik (2013)
In order to maintain stable and accessible production areas in LKABs underground mining operations in Kiruna and Malmberget, the amount of rock support has increased in recent years. Support is installed systematically, with fibre-reinforced shotcrete and cement-grouted modified Kiruna bolts as two of the main support elements. Since both of these are based on cement, the full design bearing capacity is only achieved some time after installation. Therefore, an understanding of the strength development process of these elements is essential in order to determine safe times for re-entry into supported drifts.Two series of field pull-out tests have been performed with modified Kiruna bolts, in two separate geological environments. For both series of tests, the rock bolts were installed using bolting rigs and then pulled successively after a number of hours. The results show that a modified Kiruna bolt achieves its designed bearing capacity after approximately 19 hours of curing during favorable rock conditions. However, the pull-out resistance showed significant scatter when performed in lower-quality rock.The development of flexural toughness for round shotcrete panels has been determined according to the standard ASTM C1550 under laboratory conditions. A stud driver was used to measure the uniaxial compressive strength for panels in the laboratory as well as for newly applied shotcrete in the field. After 15 hours of curing, 468 J of energy absorption was achieved under field conditions. This is lower than the requirement of 650 J. According to the litterature review, drilling through the shotcrete can be permitted when the UCS exceeds 1.6 MPa. This was achieved after less than 4.5 hours in the field. Validerat; 20130529 (global_studentproject_submitter)